Non-isothermal crystallization of aqueous nanofluids with high aspect-ratio carbon nano-additives for cold thermal energy storage. (15th January 2015) - Fan, Li-Wu; Yao, Xiao-Li; Wang, Xiao; Wu, Yu-Yue; Liu, Xue-Ling; Xu, Xu; Yu, Zi-Tao
Highlights: Aqueous nanofluids with CNTs or GNPs were prepared for cold thermal energy storage. Non-isothermal crystallization of the aqueous nanofluids was tested by DSC method. The supercooling degree reduces due to the nucleating effect of the nanoparticles. GNPs in general lead to greater drops of latent heat of crystallization than CNTs. The crystallization rates were shown to vary by crystallization kinetics analysis. Abstract: Non-isothermal crystallization of aqueous nanofluids in the presence of two types of high aspect-ratio carbon nano-additives, i.e., carbon nanotubes (CNTs) and graphene nanoplatelets (GNPs), was characterized by means of differential scanning calorimetry (DSC). A parametric investigation was performed on various concentrations of the nanofluids as well as various cooling rates during the DSC tests. In addition to the supercooling degree and latent heat of crystallization, the crystallization kinetics was also analyzed by both the Ozawa method and a modified Ozawa-based method. It was shown that dilute loading of CNTs or GNPs leads to reduction of the supercooling degree up to 5 °C due to the nucleating effect. The planarly-shaped GNPs featuring large contact area perform better than CNTs in facilitating heterogeneous nucleation, which greatly suppress crystal growth during the late phase of non-isothermal crystallization. In contrast to the case of GNPs, CNTs may be able to accelerate crystallization up to nearly 37% at relatively dilute loadings, especially when the cooling rate is low. The CNT-based aqueous nanofluids exhibit more balanced performance in supercooling degree, latent heat of crystallization, and crystallization kinetics, which may be utilized as an emerging candidate of phase change materials for cold thermal energy storage.